All-Internal Limb Lengthening with Simultaneous Corrective Osteotomy After Internal Hemipelvectomy: A Case Report. Issue 2 (12th April 2022) - Femino, Joseph D.; Nelson, Scott C.; Agulnik, Mark; Zuckerman, Lee M.
Abstract : Case: A 27-year-old woman with a Grade II chondrosarcoma in the right acetabulum underwent a Type II internal hemipelvectomy with an ischiofemoral fusion. She developed a 7.0-cm functional limb-length discrepancy with adduction of the hip at rest. Four years after surgery, she underwent a corrective osteotomy and limb lengthening with a magnetic lengthening nail. Eleven years after tumor resection and a successful pregnancy, she had symmetric leg lengths and ambulated without an assistive device. Conclusions: A magnetic lengthening nail is a viable option for correcting limb-length discrepancies after hemipelvectomy. If necessary, a simultaneous corrective proximal femoral osteotomy can be performed.